Pengaruh Jenis Plankton yang Berbeda Terhadap Kelulushidupan dan Laju Pertumbuhan Larva Teripang Pasir (Holothuria Scabra) pada Fase Planktonik - Yunita Safitri; Dwi Mardhia; Dedi Syafikri; Neri Kautsari (Indonesian Journal of Applied Science and Technology, 2020)
Sea cucumbers are phytoplankton and zooplankton (natural food) eating organisms. Availability or concentration of feed plays an important role in the growth and survival of larvae. Three types of plankton used in this study are diatom species, namely Nanocloropsys sp, Isochrysis sp and pavlopa sp which have high nutritional content and are commonly cultivated. This research was conducted to find the right and optimal type of feed in increasing the production of survival rate and growth rate of larvae of sea cucumbers (Holothuria scabra) so that the cultivation of sea cucumbers can succeed. This research was conducted in the village of Teluk Santong, Plampang District, Sumbawa Regency. The experimental design used in this study was a Completely Randomized Design (CRD) with 3 replications and 4 treatments placed at random. The results showed that the highest growth rate and survival rate of sea cucumber larvae was obtained from the treatment of Isochrysis sp. The value of the growth rate of sea cucumber larvae was 62.7 µm and the survival value was 93.33%, while the lowest growth and survival rate was in the control treatment with a growth rate value of 49.4 µm and a survival rate of 9.33%,